Choroidal thickness in lupus nephritis. (February 2020) - Lee, I; Marshall, B; Ranganathan, P; Eisen, S; Rajagopal, R; Kim, A H J; Li, T
Objective: This study aimed to compare choroidal thickness between patients with systemic lupus erythematosus (SLE) and lupus nephritis (LN) in complete renal remission to that of patients with SLE without LN. Methods: This was a retrospective case-control study of 23 SLE patients meeting either the American College of Rheumatology or Systemic Lupus International Collaborating Clinics classification criteria and followed at Washington University School of Medicine Rheumatology or Nephrology, and Ophthalmology outpatient clinics. The diagnosis of LN was based on renal pathology, and complete renal remission was defined as proteinuria <500 mg/daily and serum creatinine at baseline. Extra-renal flare status was determined using modified Fortin criteria. Choroidal thickness was measured using spectral-domain optical coherence tomography and read by blinded reviewers. Results: In SLE patients without extra-renal flare, choroidal thickness of LN patients was 281 ± 78 µm compared to 288 ± 70 µm in non-LN SLE patients ( p = 0.766) at the fovea. Conclusion: Choroidal thickness was not different in patients with LN in remission compared to non-LN SLE patients in remission. Additional studies are needed to examine choroidal thickness in patients with SLE with active LN.